Influence ofaccelerated aging on the wear behavior of cross-linked polyethylene liners: a hip simulator study - Dammer, Rebecca; Zietz, Carmen; Reinders, Jörn; Teske, Michael; Bader, Rainer (Journal of Clinical Medicine, 2022)
Sequential cross-linked and annealed ultra-high-molecular-weight polyethylene (SX-PE) is known as a low-wear articulating partner, especially for total hip endoprostheses. Aging of polymeric materials, irrespective of if induced by shelf or in vivo life, can degrade their tribological and mechanical properties. However, changes in wear behavior of aged SX-PE liners have not been not quantified so far. An accelerated aging procedure, to simulate shelf and in vivo aging, was performed on thin SX-PE liners after five million load cycles using a simulator (“worn-aged”) as well as on new SX-PE liners (“new-aged”). A subsequent hip simulator test was performed with both thin SX-PE liner sets in combination with large-diameter ceramic femoral head, representing a combination known as advantageous for treatment after revision because of dislocation. Oxidation indices were measured on the liners after each step of the procedure. SX-PE liners after accelerated aging show bedding-in phases during simulator test, which was a characteristic only known from clinical investigations. Hence, the wear rates of the “new-aged” ((1.71 ± 0.49) mg/million cycles) and of the “worn-aged” ((9.32 ± 0.09) mg/million cycles) SX-PE were increased in the first period compared to new unaged SX-PE liners. Subsequently, the wear rates decreased for “new-aged” and “worn-aged” inserts to (0.44 ± 0.48) mg/million cycles and (2.72 ± 0.05) mg/million cycles, respectively. In conclusion, the results show promising effects of accelerated aging on SX-PE liners in simulator testing and for potential long-term use in clinical applications.
Gesehen am 31.10.2022